(untitled) (Journal of the College of Basic Education, 2022)
The current study is mainly devoted to explore whether the Iraqi secondary school students’ attitudes towards the English language itself, the English language community and culture plays a significant role in motivating them to learn English. The research sample is a group of 40 5th grade secondary school students. The instrument of the study is a questionnaire that measures the learner’s awareness with the declarations of the above variables. To sum up, the findings of the data analysis of given above, the following conclusions can be made: Most of the subjects of the sample are interested in reading about English culture and community, so as to be able to develop their reading and speaking ability. Some of subjects of the sample think that their own morals , specifically the Iraqi ones , can be negatively influenced by the culture and values of English-speaking countries .